Energy expenditure and enjoyment of instructor-led exercise videos for children ages 7–13 - Habring, Mariam A.; Friday, Penelope J.; Schwartz, Anna; Abbas, Hala I.; Beemer, Lexie R.; Hasson, Rebecca E. (PLOS ONE, 2025)
Background The Interrupting Prolonged sitting with ACTivity (InPACT) at Home intervention provides youth with access to virtual, instructor-led exercise videos to promote physical activity in the home. While this program has had statewide reach, there is a need to understand the efficacy of the exercise videos to (1) induce positive cardiometabolic benefits in youth and (2) promote exercise enjoyment in the home. Purpose The purpose of this study was to determine and compare the effects of the InPACT at Home exercise videos on physical activity energy expenditure and physical activity enjoyment in children ages 7–13 years. Methods Thirty-nine participants ages 7–13 years were recruited to participate in this study. Participants completed five, 8-minute InPACT at Home exercise videos (cardio, strength, sports skills, and mindfulness) and one, 8-minute control video (sedentary). Physical activity energy expenditure was assessed using indirect calorimetry. Physical activity enjoyment was assessed using the Physical Activity Enjoyment Scale. Results Exercise videos elicited significantly higher physical activity energy expenditure and enjoyment compared to the control video (p < 0.05). There were also significant differences in physical activity energy expenditure by video type with the highest energy expenditure recorded during the cardio videos (24.84 ± 9.14 kcals) followed by the strength (20.97 ± 9.97 kcals), sports skills (20.66 ± 7.72 kcals), and mindfulness videos (17.34 ± 7.80 kcals, p < 0.05). There were no significant differences in physical activity enjoyment by exercise video type (all p’s > 0.05). Conclusion On average, children expended approximately 22 kcals while engaging in the InPACT at Home videos and rated all the videos as enjoyable. These findings highlight the potential of the InPACT at Home intervention to provide sustainable opportunities for youth to engage in health-enhancing physical activity in the home.